Helix insertion into bilayers and the evolution of membrane proteins - Renthal, Robert (2009)
Polytopic α-helical membrane proteins cannot spontaneously insert into lipid bilayers without assistance from polytopic α-helical membrane proteins that already reside in the membrane. This raises the question of how these proteins evolved. Our current knowledge of the insertion of α-helices into natural and model membranes is reviewed with the goal of gaining insight into the evolution of membrane proteins. Topics include: translocon-dependent membrane protein insertion, antibiotic peptides and proteins, in vitro insertion of membrane proteins, chaperone-mediated insertion of transmembrane helices, and C-terminal tail-anchored (TA) proteins. Analysis of the E. coli genome reveals several predicted C-terminal TA proteins that may be descendents of proteins involved in pre-cellular membrane protein insertion. Mechanisms of pre-translocon polytopic α-helical membrane protein insertion are discussed.